Carbosilane Glycodendrimers for Anticancer Drug Delivery: Synthetic Route, Characterization, and Biological Effect of Glycodendrimer-Doxorubicin Complexes - Müllerová, Monika; Maciel, Dina; Nunes, Nádia; Wrobel, Dominika; Stofik, Marcel; Červenková Št Astná, Lucie; Krupková, Alena; Cuřínová, Petra; Nováková, Kateřina; Božík, Matěj; Malý, Marek; Malý, Jan; et al. (Biomacromolecules, 2022)
The complexity of drug delivery mechanisms calls for the development of new transport system designs. Here, we report a robust synthetic procedure toward stable glycodendrimer (glyco-DDM) series bearing glucose, galactose, and oligo(ethylene glycol)-modified galactose peripheral units. In vitro cytotoxicity assays showed exceptional biocompatibility of the glyco-DDMs. To demonstrate applicability in drug delivery, the anticancer agent doxorubicin (DOX) was encapsulated in the glyco-DDM structure. The anticancer activity of the resulting glyco-DDM/DOX complexes was evaluated on the noncancerous (BJ) and cancerous (MCF-7 and A2780) cell lines, revealing their promising generation- and concentration-dependent effect. The glyco-DDM/DOX complexes show gradual and pH-dependent DOX release profiles. Fluorescence spectra elucidated the encapsulation process. Confocal fluorescence microscopy demonstrated preferential cancer cell internalization of the glyco-DDM/DOX complexes. The conclusions were supported by computer modeling. Overall, our results are consistent with the assumption that novel glyco-DDMs and their drug complexes are very promising in drug delivery and related applications.
Keywords: Humans; Cell Line, Tumor; Female; Antineoplastic Agents; doxorubicin; uvolňování léčiv; Polyethylene Glycols; lidé; ženské pohlaví; Drug Liberation; nádory vaječníků; silany; Silanes; Drug Carriers; Drug Delivery Systems; nádorové buněčné linie; lékové transportní systémy; nosiče léků; Ovarian Neoplasms; protinádorové látky; polyethylenglykoly; Doxorubicin